The Role of the Cytoskeleton in Regulating the Natural Killer Cell Immune Response in Health and Disease: From Signaling Dynamics to Function - Ben-Shmuel, Aviad; Sabag, Batel; Biber, Guy; Barda-Saad, Mira (Frontiers in Cell and Developmental Biology, 2021)
Natural Killer (NK) cells are innate lymphoid cells, which play key roles in elimination of virally infected and malignant cells. The balance between activating and inhibitory signals derived from NK surface receptors govern the NK cell immune response. The cytoskeleton facilitates most NK cell effector functions, such as motility, infiltration, conjugation with target cells, immunological synapse assembly, and cytotoxicity. Though many studies have characterized signaling pathways that promote actin reorganization in immune cells, it is not completely clear how particular cytoskeletal architectures at the immunological synapse promote effector functions, and how cytoskeletal dynamics impact downstream signaling pathways and activation. Moreover, pioneering studies employing advanced imaging techniques have only begun to uncover the architectural complexity dictating the NK cell activation threshold; it is becoming clear that a distinct organization of the cytoskeleton and signaling receptors at the NK immunological synapse plays a decisive role in activation and tolerance. Here, we review the roles of the actin cytoskeleton in NK cells. We focus on how actin dynamics impact cytolytic granule secretion, NK cell motility, and NK cell infiltration through tissues into inflammatory sites. We will also describe the additional cytoskeletal components, non-muscle Myosin II and microtubules that play pivotal roles in NK cell activity. Furthermore, special emphasis will be placed on the role of the cytoskeleton in assembly of immunological synapses, and how mutations or downregulation of cytoskeletal accessory proteins impact NK cell function in health and disease.